2018
DOI: 10.1016/j.ymthe.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Coding for Interleukin-2 and Tumor Necrosis Factor Alpha Replaces Lymphodepleting Chemotherapy in Adoptive T Cell Therapy

Abstract: Lymphodepleting preconditioning with high-dose chemotherapy is commonly used to increase the clinical efficacy of adoptive T cell therapy (ACT) strategies, however, with severe toxicity for patients. Conversely, oncolytic adenoviruses are safe and, when engineered to express interleukin-2 (IL-2) and tumor necrosis factor alpha (TNF-α), they can achieve antitumor immunomodulatory effects similar to lymphodepletion. Therefore, we compare the safety and efficacy of such adenoviruses with a cyclophosphamide- and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 52 publications
0
46
0
2
Order By: Relevance
“…Oncolytic replication is also important, but perhaps chiefly because of its immunostimulatory consequences. Ad5/3-E2F-d24-hTNFa-IRES-hIL2 (TILT-123) is an engineered oncolytic adenovirus with chimeric serotype 5/3 designed specifically to be coupled with T-cell-related therapies such as adoptive-cell transfer 18 (such as chimeric antigen receptor [CAR] T-cell therapy 19 ) or ICIs. 20 To go beyond the inherent immunostimulatory activity of the presence of adenovirus in tumors, TILT-123 was tailored to enhance the antitumor effect of CD8 T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Oncolytic replication is also important, but perhaps chiefly because of its immunostimulatory consequences. Ad5/3-E2F-d24-hTNFa-IRES-hIL2 (TILT-123) is an engineered oncolytic adenovirus with chimeric serotype 5/3 designed specifically to be coupled with T-cell-related therapies such as adoptive-cell transfer 18 (such as chimeric antigen receptor [CAR] T-cell therapy 19 ) or ICIs. 20 To go beyond the inherent immunostimulatory activity of the presence of adenovirus in tumors, TILT-123 was tailored to enhance the antitumor effect of CD8 T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it had been demonstrated that oncolytic adenoviruses express interleukin-2 (IL-2), and the tumor necrosis factor alpha (TNF-a) can achieve an anti-tumor immunomodulatory effect similar to lymphodepletion. Importantly, using an oncolytic adenovirus is much safer than Lymphodepleting preconditioning with high-dose chemotherapy (106). According to Sun et al's study, rAd-IL-2 exhibits a significant induced anti-tumor immune response by recruiting CD4 + and CD8 + T cells, increasing the interferon-γ release, and stimulating cytotoxic T lymphocyte responses in the HCC tumor model (53).…”
Section: Modulation Of the Host Immune Response Triggered By Oncolytimentioning
confidence: 99%
“…A recent trial found regulated expression of recombinant IL-12, following intratumoral injection of Ad-RTS-hIL-12 in combination with oral veledimex, to be safe in 31 patients with recurrent glioblastoma [42]. In addition to IL-12, several other interleukins, including IL-2, IL-24 and IL-13, have been used to arm oncolytic adenovirus and have shown promising immune-activating properties in multiple preclinical cancer models [43][44][45].…”
Section: Immunostimulatory Molecules-expressing Adenovirus Vectorsmentioning
confidence: 99%